Thrombectomy in DAWN- and DEFUSE-3-Ineligible Patients: A Subgroup Analysis From the BEST Prospective Cohort Study. Issue 2 (23rd November 2019) - Siegler, James E; Messé, Steven R; Sucharew, Heidi; Kasner, Scott E; Mehta, Tapan; Arora, Niraj; Starosciak, Amy K; De Los Rios La Rosa, Felipe; Barnhill, Natasha R; Mistry, Akshitkumar M; Patel, Kishan; Assad, Salman; et al.
Abstract: BACKGROUND: Because of the overwhelming benefit of thrombectomy for highly selected trial patients with large vessel occlusion (LVO), some trial-ineligible patients are being treated in practice. OBJECTIVE: To determine the safety and efficacy of thrombectomy in DAWN/DEFUSE-3-ineligible patients. METHODS: Using a multicenter prospective observational study of consecutive patients with anterior circulation LVO who underwent late thrombectomy, we compared symptomatic intracerebral hemorrhage (sICH) and good outcome (90-d mRS 0-2) among DAWN/DEFUSE-3-ineligible patients to trial-eligible patients and to untreated DAWN/DEFUSE-3 controls. RESULTS: Ninety-eight patients had perfusion imaging and underwent thrombectomy >6 h; 46 (47%) were trial ineligible (41% M2 occlusions, 39% mild deficits, 28% ASPECTS <6). In multivariable regression, the odds of a good outcome (aOR 0.76, 95% CI 0.49-1.19) and sICH (aOR 3.33, 95% CI 0.42-26.12) were not different among trial-ineligible vs eligible patients. Patients with mild deficits were more likely to achieve a good outcome (aOR 3.62, 95% CI 1.48-8.86) and less sICH (0% vs 10%, P = .16), whereas patients with ASPECTS <6 had poorer outcomes (aOR 0.14, 95% CI 0.05-0.44) and more sICH (aOR 24, 95% CI 5.7-103). Compared to untreated DAWN/DEFUSE-3 controls, trial-ineligible patients had more sICH (13%BEST vs 3%DAWN [ P = .02] vs 4%DEFUSE [ P = .05]), but were more likely to achieve a good outcome at 90 d (36%BEST vs 13%DAWN [ P < .01] vs 17%DEFUSE [ P = .01]). CONCLUSION: Thrombectomy is used in practice for some patients ineligible for the DAWN/DEFUSE-3 trials with potentially favorable outcomes. Additional trials are needed to confirm the safety and efficacy of thrombectomy in broader populations, such as large core infarction and M2 occlusions.